2014
DOI: 10.1371/journal.pone.0100577
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Phenology of Three Dwarf Shrub Species in a Six-Year Soil Warming Experiment at the Alpine Treeline

Abstract: Global warming can have substantial impacts on the phenological and growth patterns of alpine and Arctic species, resulting in shifts in plant community composition and ecosystem dynamics. We evaluated the effects of a six-year experimental soil warming treatment (+4°C, 2007–2012) on the phenology and growth of three co-dominant dwarf shrub species growing in the understory of Larix decidua and Pinus uncinata at treeline in the Swiss Alps. We monitored vegetative and reproductive phenology of Vaccinium myrtill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…in the Pyrenees and the Alps, is hence likely to change vegetation again, but in combination with climate change it is unlikely that vegetation will change back to its previous composition. Elevated atmospheric CO 2 concentrations did not enhance plant growth in alpine grasslands (Inauen et al 2012;Korner et al 1997) but in shrub communities at treeline (Anadon-Rosell et al 2014;Dawes et al 2013Dawes et al , 2014 where the bilberry (Vaccinium myrtillus) showed more growth, possibly at the cost of smaller or less responsive plant species.…”
Section: Extensive Monitoring Of Recent Changes In Summit Plantsmentioning
confidence: 98%
“…in the Pyrenees and the Alps, is hence likely to change vegetation again, but in combination with climate change it is unlikely that vegetation will change back to its previous composition. Elevated atmospheric CO 2 concentrations did not enhance plant growth in alpine grasslands (Inauen et al 2012;Korner et al 1997) but in shrub communities at treeline (Anadon-Rosell et al 2014;Dawes et al 2013Dawes et al , 2014 where the bilberry (Vaccinium myrtillus) showed more growth, possibly at the cost of smaller or less responsive plant species.…”
Section: Extensive Monitoring Of Recent Changes In Summit Plantsmentioning
confidence: 98%
“…; Anadon‐Rosell et al . ), the responses of prostrate shrubs, particularly deciduous species, to warming and snowmelt change have been relatively understudied (but see Clemmensen & Michelsen ; Kudo et al . ), and rarely so for both factors in combination.…”
Section: Introductionmentioning
confidence: 99%
“…For the Vaccinium species, the amount of N per leaf increased during the first 2 weeks after labelling, during leaf expansion (Anadon‐Rosell et al . ), and then decreased slightly from 2 to 7 weeks ( V. gaultherioides : F 1,54 = 6·98, P = 0·011; V. myrtillus : F 1,62 = 4·31, P = 0·042; Fig. g,h).…”
Section: Resultsmentioning
confidence: 93%
“…Shoot expansion of this species started in the season and was >80% complete at 4 weeks after label application (Anadon‐Rosell et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation